EPID-33. GENDER-SPECIFIC PROBABILISTIC ATLASES OF GLIOBLASTOMA REVEAL IMPACT OF TUMOR LOCATION ON PROGRESSION FREE SURVIVAL. (11th November 2019) - Beig, Niha; Ismail, Marwa; Saeed Bamashmos, Anas; Statsevych, Volodymyr; Hill, Virginia; Madabhushi, Anant; Ahluwalia, Manmeet; Tiwari, Pallavi
Abstract: BACKGROUND: Recent epidemiological studies suggest that gender differences in Glioblastoma (GBM) influence the prognostic outcome of patients, and thus should be considered for patient management. In this feasibility study, we developed population atlases of pre-treatment MRI lesions to evaluate whether progression free survival (PFS) in gender-specific GBM patients have a spatial proclivity to hemispheric or lobe-specific locations. METHODS: 203 pre-operative MRI sequences (1.5T/3T T1w, T2w, FLAIR scans, multi-center) of GBM (125 males [m] & 78 females [f]) from TCIA (n=130), Ivy-GAP (n=32) and participating institution (n=41), along with PFS (median cut-off =189 days [m], 78 days [f]) were analysed. Frequency atlases (improved PFS [i-PFS] & worse PFS [ω-PFS]) of tumor occurrence in T2/FLAIR hyperintense regions were developed for each gender, by averaging voxel intensities across all patients. To compute significant differences (p-value< 0.05), voxel-based analysis of differential involvement (ADIFFI) based on two-tailed Fisher's exact test was performed on (a) m: i-PFS (n= 61) vs m: ω-PFS (n= 62), and (b) f: i-PFS (n= 39) vs f: ω-PFS (n= 39) atlases. Prominent clusters were identified and mapped to LONI Probabilistic Brain Atlas (LPBA40) parcellations to provide anatomic localization for each gender's PFS. RESULTS: ADIFFI analysis revealed that m: i-PFS tumors were more often localized to the inferior frontal gyrus of left hemisphere with a frequency of 20% whereas m: ω-PFS were more often localized to the right insular cortex (p< 0.005). f: i-PFS tumors were more often localized to the right hemisphere in the parietal and temporal lobe, while f: ω-PFS had 15.7% occurrence in the superior and middle frontal gyri of the right hemisphere (p< 0.03). CONCLUSION: Our analysis suggests spatial proclivity of gender-specific PFS to hemispheric and lobe-specific locations in the brain. Gender-specific prognostic models and nomograms may be more accurate than unisex models and nomograms for GBM patients.